Case Report: Identification of a novel mutation, c.1067T > A, in the SERPING1 gene in a Chinese male with type 1 hereditary angioedema - Du, Wenjin; Yang, Ke; Zhang, Qiuxing; Lin, Xianghua; Zhang, Wenchao; Guo, Weili; Meng, Zhaoji; Wang, Siqin (Frontiers in Allergy, 2025)
Hereditary angioedema (HAE) is a rare autosomal dominant genetic disorder characterized by recurrent, unpredictable episodes of angioedema that commonly involve the face, limbs, respiratory tract, and gastrointestinal tract. Clinical presentations vary substantially among individuals, increasing the likelihood of misdiagnosis or missed diagnosis. In severe cases, if not properly managed, laryngeal edema can result in asphyxiation or even death. Here, we report a Chinese male patient who experienced recurrent limb swelling and abdominal pain. Laboratory tests revealed low levels of complement C4 and C1 inhibitors, along with impaired C1 inhibitor function. Genomic DNA extracted from peripheral blood samples underwent PCR amplification and Sanger sequencing, which identified a de novo heterozygous mutation in the SERPING1 gene at chr11:57379227, confirming a novel missense mutation NM_000062.c.1067T > A (p.V356E). Ultimately, the patient was diagnosed with HAE-C1INH-Type1 and successfully protected from recurrent attacks through subcutaneous administration of lanadelumab.